Clinical, neuroimaging and prognostic study of 127 cases with infarction of the corpus callosum. (11th April 2019) - Sun, X.; Li, J.; Fan, C.; Zhang, H.; Si, Y.; Fang, X.; Guo, Y.; Zhang, J. H.; Wu, T.; Ding, S.; Bi, X.
Abstract : Background and purpose: The aim of this study was to retrospectively investigate clinical and neuroimaging characteristics in the largest sample size of patients with corpus callosum infarction to date and then to follow up these patients for 1 year to clarify the prognosis of this rare stroke entity. Methods: A total of 127 patients with acute callosal infarction out of 5584 acute ischaemic stroke patients were included in this study. The recruited patients were divided into a pure callosal infarction group and a complex callosal infarction group (coupled with other infarct locations simultaneously), and clinical and neuroimaging features were analyzed. Some of the patients were followed up for 1 year to evaluate recurrence rate and mortality. Results: The incidence of acute callosal infarction was 2.3%. Most patients presented with advanced neurological dysfunction with or without mild to moderate motor or sensory disorders on admission. The negative rate of computed tomography scan was still 76.4% even at >24 h after onset. Large‐artery atherosclerosis was the most common etiological type. Compared with complex callosal infarction, the pure callosal infarction group had more mental disorders ( P = 0.030). Compared with common basal ganglia infarction, the pure callosal infarction group had better short‐term recovery ( P = 0.016) but higher 1‐year mortality ( P = 0.037). Age and mental disorders were independent risk factors for death in callosal infarction. Conclusions: Callosal infarction is a white matter stroke that occurs with low incidence. Elderly patients with vascular risk factors showed sudden mental or cognitive disorders and callosal infarction could not be excluded. More attention should be paid to the early diagnosis and secondary prevention of callosal infarction because of its poor long‐term outcome.